To Be or Not to Be? 教職召喚與專業認同對藝術大學師資生生涯決策自我效能、結果期待及生涯希望感的調節效果分析 To Be or Not to Be? An Analysis of the Moderating Effects of Teaching Calling and Professional Identity on Career Decision-Making Self-Efficacy, Outcome Expectations, and Career Hope Among Pre-Service Teachers in Arts Universities - 陳嘉成 Chia-Cheng Chen; 洪兆祥 Chao-Hsiang Hung; 鄧鈞文 Chun-Wen Teng; 劉孟芳 Meng-Fang Liu (Journal of Research in Education Sciences)
藝術大學師資生在培育過程中會遭遇許多生涯阻礙因素，這些因素都會影響師資生未來是否從事已學習多年的藝術專業工作或成為藝術教師的生涯決定。生涯希望感是師資生成為初任教師後是否容易耗損的重要指標，而生涯決策自我效能與結果期待是貫穿許多生涯發展模式的核心架構，因此，本研究以國內某藝術大學475位師資生為研究對象，探討教職召喚與專業認同對藝術大學師資生生涯決策自我效能、結果期待及生涯希望感的交互影響關係。結果發現：一、師資生教職召喚量表具有良好之信度與效度，且內在熱情與外在誘因兩個因素間呈現斜交關係，表示現代的師資生抱持著多元召喚而非二擇一；二、師培認同是師資生生涯發展的關鍵變項，只有確認自己未來願意從事教職的人才會有較高的生涯希望；三、專業認同與教職召喚的調節效果，存在「確定且特定」的時序關係，專業認同的影響在前，而教職召喚的影響在後；四、同時採用「高內在熱情／高外在誘因」的師資生，由於處在雙趨衝突的狀態，導致生涯希望感卻是最低的。最後，本研究根據分析結果對藝術類科師資培育提出教學現場與生涯輔導的相關建議。 Research Motivation and Objectives The motivation behind this study stems from the unique career development challenges faced by pre-service teachers at art universities. Unlike their counterparts at other institutions, these students often juggle demanding artistic practices with teacher training programs. This study aims to explore how career self-efficacy and outcome expectations influence career hope among these pre-service teachers. Furthermore, it investigates the moderating roles of professional identity and teaching calling in these relationships, providing a comprehensive understanding of the career development processes in this specific educational context. Literature Review The theoretical framework of this study is based on the Social Cognitive Career Theory (SCCT) proposed by Lent et al. (1994), which emphasizes the role of cognitive mediators in social perception. SCCT has been extensively validated and applied across various domains. This theory identifies career self-efficacy and outcome expectations as core constructs influencing career development. Previous studies have shown that these constructs are pivotal in shaping career interests, choices, performance, and overall well-being. Additionally, professional identity, as a resource allocation strategy, and teaching calling, as a motivational factor, are crucial in understanding the career trajectories of pre-service teachers. Professional identity refers to the alignment of an individual’s self-concept with their professional roles and responsibilities. For pre-service teachers at art universities, professional identity encompasses both their artistic and teaching aspirations. Previous studies have shown that a strong professional identity is crucial for sustained career commitment and reducing burnout. Teaching calling, a concept rooted in career calling, emphasizes the intrinsic passion and sense of purpose associated with the teaching profession. Research indicates that individuals with a strong teaching calling are more likely to find meaning and satisfaction in their work, which enhances their career commitment and overall well-being. In the context of pre-service teachers, teaching calling is influenced by both intrinsic motivations (e.g., a passion for teaching) and extrinsic factors (e.g., job stability and societal respect). Research Methods Participants: The study targeted students enrolled in a teacher training program at a national art university in 2023. A total of 482 responses were collected through online surveys, with 475 valid samples (98.54% validity rate). The sample comprised 79.2% female and 20.8% male students. Instruments Career Self-Efficacy Scale This scale, adapted from Betz (1994) and Hackett and Betz (1981), assesses individuals’ confidence in their ability to successfully engage in career decision-making activities. It includes eight items, divided into two subscales: goal selection (e.g., “I am confident about choosing a career that I will like”) and problem-solving (e.g., “I know what resources are available to help me overcome career-related obstacles”). Responses are measured on a 4-point Likert scale, with higher scores indicating greater self-efficacy. The Cronbach’s alpha coefficients for these subscales were .86 and .82, respectively. Outcome Expectations Scale This scale was developed specifically for this study based on Chen and Hung’s (2020) work. It includes five items measuring students’ expectations regarding the benefits of completing their teacher training (e.g., “Completing my teacher training will significantly help me in my future teaching career”). Items are rated on a 4-point Likert scale, with higher scores indicating more positive outcome expectations. The scale demonstrated good internal consistency with a Cronbach’s alpha of .83. Career Hope Scale Adapted from Snyder (2002) and Huang et al. (2014), this scale measures students’ hope regarding their future teaching careers. It consists of 14 items across two dimensions: pathways thinking (e.g., “I can think of many ways to reach my career goals”) and agency thinking (e.g., “I energetically pursue my career goals”). Responses are given on a 4-point Likert scale, with higher scores indicating higher career hope. The overall reliability (Cronbach’s alpha) of the scale was .91. Professional Identity Scale Developed based on Lally and Kerr (2005), this single-item measure assesses students’ professional identity by asking, “Do you see yourself more as an artist or a teacher? ” Responses range from 1 (I only see myself as an artist) to 4 (I only see myself as a teacher). For analysis, responses were dichotomized into two groups: those identifying more with their artistic profession (responses 1 and 2) and those identifying more with the teaching profession (responses 3 and 4). Teaching Calling Scale This scale was created based on the work of Dik et al. (2012) and Wang and Wu (2017), tailored to the context of pre-service teachers. It includes 10 items divided into two subscales: intrinsic passion (e.g., “Becoming a teacher is my true calling”) and external incentives (e.g., “Job stability is a significant reason for me to pursue teaching”). Items are rated on a 4-point Likert scale, with higher scores indicating a stronger teaching calling. The Cronbach’s alpha coefficients were .90 for intrinsic passion and .79 for external incentives. Data Analysis Confirmatory factor analysis (CFA) and path analysis were conducted using SPSS 21.0 and AMOS 21. The moderation effects of professional identity and teaching calling were tested using the PROCESS macro for SPSS, with bootstrap methods applied to validate the significance of indirect effects. Research Results Descriptive Statistics and Correlations All continuous variables, including career self-efficacy, outcome expectations, and career hope, showed acceptable levels of normality. The correlations between these variables were significant, confirming the expected relationships proposed by SCCT. Path Model and Mediation Effects The path analysis revealed that career self-efficacy had a significant direct effect on career hope. Outcome expectations partially mediated this relationship, indicating that students’ beliefs about their future outcomes influence their overall career hope. Moderation Effects: The study tested two moderation models: -Model A: Teaching calling moderates the effect of career self-efficacy on outcome expectations. -Model B: Professional identity moderates the relationship between outcome expectations and career hope. The data supported Model B, suggesting that professional identity plays a critical role in the early stages of career development, while teaching calling is more influential in later stages. Discussion The findings highlight the importance of enhancing career self-efficacy among pre-service teachers to foster career hope. Teaching calling, particularly intrinsic passion, significantly boosts career hope for students with high outcome expectations. However, a combination of high intrinsic passion and high external incentives can paradoxically lower career hope, likely due to conflicting motivations. Professional identity, as a resource allocation strategy, emerges as a key factor in career development. Students who prioritize their professional identity as teachers over their artistic identity are more likely to sustain their career aspirations and avoid burnout. Recommendations For teacher training institutions: 1. Enhance Career Self-Efficacy: Provide comprehensive career development resources and training to help students navigate the challenges of becoming teachers. This includes information on the teaching profession and preparation for certification exams. 2. Support Professional Identity Development: Organize activities that help students clarify their professional identity and align it with their career goals. This can reduce burnout and increase career hope. 3. Balance Intrinsic and Extrinsic Motivations: Encourage students to find a balance between their intrinsic passion for teaching and the external incentives, ensuring that they do not fall into a state of motivational conflict. In conclusion, this study provides valuable insights into the career development of pre-service teachers at art universities. By understanding the roles of career self-efficacy, outcome expectations, professional identity, and teaching calling, educators and policymakers can better support these students in achieving their career aspirations.